Comportamento dos consumidores de frutas e hortaliças: um survey na região central do Rio Grande do Sul - Gonçalves, Thaís Arrué Melo (2017)
Consumption is a bilateral relationship, where the good is acquired through the relationship between at least two individuals, and an analysis of consumption is important through the approach of some aspects of economic theory, trying to understand the influence of theoretical elements on consumer behavior. The neoclassical theory analyzes the individual as a rational being, who carries out his purchases based on price and budget constraints. The Institutional Economy is a branch of Economic Theory and is subdivided into two strands: The Institutional Economy (or Old Institutional Economy) and the New Institutional Economy. Throughout this study both theories were used to carry out the analysis, where the first one has its focus on the consumption habits and the second slope in the transactions. Thus the focus of the research is to analyze the behavior of consumers in the central region of RS in the light of economic theories. The methodology used was a survey carried out in the municipality of Santa Maria - RS, main commercial center in the central region of RS. We interviewed 384 consumers, randomly approached in supermarkets and road, the stratification used by the research was income, as well as for data analysis. In general, the result showed that the lower income consumers show a behavior of the postulates of the neoclassical theory, due to budgetary constraints, with the strong influence of prices. The consumers with intermediate incomes are influenced by aspects of habits and preferences, according to the institutional economy. And consumers with incomes above five minimum wages are more concerned with aspects of transaction costs than the new institutional economy, but consumers who value these theory-related aspects most are consumers with incomes above fifteen minimum wages. The consumption of fruits and vegetables increased in concomitance with the income of the consumers, as well as consumption of organic products and certificates.